Synthesis of borate cross-linked rhamnogalacturonan II - Funakawa, Hiroya; Miwa, Kyoko (Frontiers in Plant Science, 2015)
In the present review, we describe current knowledge about synthesis of borate crosslinked rhamnogalacturonan II (RG-II) and it physiological roles. RG-II is a portion of pectic polysaccharide with high complexity, present in primary cell wall. It is composed of homogalacturonan backbone and four distinct side chains (A-D). Borate forms ester bonds with the apiosyl residues of side chain A of two RG-II monomers to generate borate dimerized RG-II, contributing for the formation of networks of pectic polysaccharides. In plant cell walls, more than 90% of RG-II are dimerized by borate under B sufficient conditions. Borate crosslinking of RG-II in primary cell walls, to our knowledge, is the only experimentally proven molecular function of boron (B), an essential trace-element. Although abundance of RG-II and B is quite small in cell wall polysaccharides, increasing evidence supports that RG-II and its borate crosslinking are critical for plant growth and development. Significant advancement was made recently on the location and the mechanisms of RG-II synthesis and borate cross-linking. Molecular genetic studies have successfully identified key enzymes for RG-II synthesis and regulators including B transporters required for efficient formation of RG-II crosslinking and consequent normal plant growth. The present article focuses recent advances on (i) RG-II polysaccharide synthesis, (ii) occurrence of borate crosslinking and (iii) B transport for borate supply to RG-II. Molecular mechanisms underlying formation of borate RG-II crosslinking and the physiological impacts are discussed.